THE COSMETIC-RELEVANT BIOLOGICAL ACTIVITIES OF OIL EXTRACTS AND PROTEIN HYDROLYSATES FROM HERMETIA ILLUCENS LARVAE: A COMPARATIVE REVIEW - Zakinah, Tri Dewi (Indonesian Journal of Cosmetics, 2025)
The cosmetic industry is increasingly seeking sustainable bioactive ingredients from novel biological sources to meet growing consumer demand for naturally derived formulations with reduced environmental impact. Black soldier fly (Hermetia illucens) larvae have emerged as a promising alternative source of cosmetic bioactives, offering advantages in sustainability, resource efficiency, and circular bioeconomy integration. This comparative review systematically analyzes cosmetic-relevant biological activities of oil extracts and protein hydrolysates derived from H. illucens larvae. A comprehensive literature search was conducted across multiple scientific databases using targeted keywords related to BSF extracts and cosmetic applications. BSF larvae oil is characterized by a lipid profile rich in lauric acid (12–52%), oleic, linoleic, and palmitic acids, resembling coconut and palm kernel oil compositions. These fatty acids contribute to antimicrobial, anti-inflammatory, antioxidant, and photoprotective activities through mechanisms including membrane disruption, enzyme inhibition, and reactive oxygen species (ROS) scavenging. BSF oil extracts show strong potential for anti-acne formulations, skin barrier enhancement, and UVB protection. Protein hydrolysates obtained through enzymatic hydrolysis contain bioactive peptides (14–25 kDa) with high antioxidant capacity (up to 72.6% free radical inhibition) and cytoprotective effects against oxidative stress. In addition, BSF larvae produce diverse antimicrobial peptides (AMPs), such as defensins and cecropins, which target both Gram-positive and Gram-negative bacteria via membrane disruption and intracellular interference. This review highlights BSF-derived ingredients as multifunctional, sustainable alternatives to conventional cosmetic actives, positioning H. illucens as a next-generation source for evidence-based cosmeceutical applications.